Increased expression of glutathione peroxidase 3 prevents tendinopathy by suppressing oxidative stress - Furuta, Haruka; Yamada, Mari; Nagashima, Takuya; Matsuda, Shuichi; Nagayasu, Kazuki; Shirakawa, Hisashi; Kaneko, Shuji (Frontiers in Pharmacology, 2023)
Tendinopathy is characterized by pain, loss of tendon strength, or rupture. Previous studies have clarified multiple risk factors, including aging and fluoroquinolone use; however, the therapeutic target remains unclear. We analyzed self-reported adverse events and the US commercial claims data and found that short-term use of dexamethasone significantly prevented both fluoroquinolone-induced and age-related tendinopathy. The tendon of rats treated systemically with fluoroquinolone exhibited mechanical fragility, histological change, and DNA damage; co-treatment with dexamethasone attenuated these effects and increased the expression of the antioxidant enzyme glutathione peroxidase 3 (GPX3). The primary role of GPX3 was validated in primary cultured rat tenocytes treated with fluoroquinolone or hydrogen peroxide, which accelerates senescence, in combination with dexamethasone or viral overexpression of GPX3. These results suggest that dexamethasone prevents tendinopathy by suppressing oxidative stress through the upregulation of GPX3. A steroid-free approach for upregulation and/or activation of GPX3 can serve as a novel therapeutic strategy for tendinopathy.